PRESERVATION OF JAWI SCRIPT TEXTBOOKS: DAYAH COMMUNITY’S ROLE IN MAINTAINING ISLAMIC EDUCATIONAL HERITAGE IN ACEH - Teuku Zulkhairi; Ibnu Hajar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Jawi script plays a significant role in the dissemination of knowledge and Malay culture, but it continues to be marginalized, including among the Malays themselves. However, a number of efforts to preserve the script are still ongoing in Aceh, Indonesia. This study aimed to examine the efforts and was conducted in Banda Aceh and Aceh Besar, two essential regions in Aceh. The data for this descriptive qualitative study was obtained through observation for three months and semi-structured interviews with nine teachers of dayah (an Islamic educational institution in Aceh) and three government officers. The data were then transcribed and analyzed in three steps, namely data condensation, data display, and data conclusion. The results of data analysis show that the preservation of the Jawi script in Aceh involves two parties, namely the the dayah community and government. The government plays a role in making regulations and policies while the community is involved in the process of using and learning the book written in Jawi script. However, the role of the community is considered more dominant and substantial in preserving the script. The preservation of the Jawi script by the Dayah community is carried out through a series of teachings of Arabic-Jawi books to the people of Aceh both in mosques, in the Dayah and other locations agreed upon by the local community.